2015
DOI: 10.1007/s11030-014-9563-1
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Cinchona alkaloids

Abstract: Nature is full of dimeric alkaloids of various types from many plant families, some of them with interesting biological properties. However, dimeric Cinchona alkaloids were not isolated from any species but were products of designed partial chemical synthesis. Although the Cinchona bark is amongst the sources of oldest efficient medicines, the synthetic dimers found most use in the field of asymmetric synthesis. Prominent examples include the Sharpless dihydroxylation and aminohydroxylation ligands, and dimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 170 publications
(164 reference statements)
1
10
0
Order By: Relevance
“…7 Instead, at least for 1b the attainment of appreciable ee values with the phthalazine ethers was rather surprising, as 4b affords essentially racemic product in the AαA of the same oxindole substrate with tert-butyl ester 2c. 8 As expected, but not always observed in the organocatalytic applications of dimeric alkaloid derivatives, 16 switching between the pseudo-enantiomeric organocatalyst 4a and 4b (Table 1, entry 6 and entry 5, respectively) caused nearly perfect inversion of the sense of asymmetric induction.…”
Section: A R T I C L E I N F O Abstractsupporting
confidence: 69%
“…7 Instead, at least for 1b the attainment of appreciable ee values with the phthalazine ethers was rather surprising, as 4b affords essentially racemic product in the AαA of the same oxindole substrate with tert-butyl ester 2c. 8 As expected, but not always observed in the organocatalytic applications of dimeric alkaloid derivatives, 16 switching between the pseudo-enantiomeric organocatalyst 4a and 4b (Table 1, entry 6 and entry 5, respectively) caused nearly perfect inversion of the sense of asymmetric induction.…”
Section: A R T I C L E I N F O Abstractsupporting
confidence: 69%
“…Readily available and inexpensive cinchona alkaloids such as quinine, quinidine, cinchonine and cinchonidine are among the most useful chirality inducers in asymmetric organocatalysis . Despite their stability to moisture and oxygen and being environmentally friendly, cinchona alkaloids possess various functionalities that are available for chemical modifications .…”
Section: Methodsmentioning
confidence: 99%
“…Cinchona-based C 2 -and C 3 -symmetric compounds have also been widely studied [20]. Jew et al demonstrated the high enantioselectivity of a novel trimeric cinchona alkaloid ammonium salt as a phase-transfer catalyst (PTC) in the catalytic asymmetric alkylation of the N-(diphenylmethylene)glycine tert-butyl ester [21].…”
Section: Introductionmentioning
confidence: 99%